Zn/In dual doping enhances the thermoelectric performance of SnTe - Lijun Wang; Xiao-Lei Shi; Meng Li; Lvzhou Li; Cuicui Dong; Pengcheng Miao; Ziyi Shen; Ningyi Yuan; Jianning Ding; Shuqi Zheng; Zhi-Gang Chen (JPhys Materials)
As a lead-free material, SnTe shows high thermoelectric potential. However, the larger energy separation of SnTe results in a substantially lower Seebeck coefficient, while the relatively lighter atomic mass of Sn contributes to high thermal conductivity, leading to relatively inferior thermoelectric performance. This study employs a simple and effective microwave synthesis method to tune band structures and introduce nano-defects into the SnTe matrix by dual doping with Zn/In. First-principles calculations indicate that Zn/In dual doping introduces energy levels, broadens the band gap to 0.53 eV, and reduces the energy difference between light and heavy hole valence bands to 0.11 eV, significantly increasing the power factor. Moreover, dual doping introduces many point defects and other nano-defects, which contribute to scattering phonons of different wavelengths and reduce the lattice thermal conductivity. As a result, the zT values of all doped samples are higher than those of pure SnTe. At 773 K, the Sn _0.98 Zn _0.01 In _0.01 Te achieves a maximum zT value of approximately 0.53, which is an increase of 60% compared to the zT for pure SnTe at the same temperature. This work demonstrates that effective dual doping using the solvothermal method is a viable strategy for improving the thermoelectric performance of SnTe.